Analysis of phytochemical constituents and antioxidant activity from the fractions of Luvunga sarmentosa root extract using LCMS/MS (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Syarpin, Permatasari S, Pujianto DA. 2023. Analysis of phytochemical constituents and antioxidant activity from the fractions of Luvunga sarmentosa root extract using LCMS/MS. Biodiversitas 24: 733-740. Luvunga sarmentosa, one of the native plants of Central Kalimantan, has been used by Dayak people, especially its root, to increase sexual activity, cure sexual dysfunction and increase male fertility. Dayak people boil the stems and roots of L. sarmentosa and drink the extract. However, studies on L. sarmentosa are still limited to phytochemical content and bioactivity screening of the root extract of L. sarmentosa. This research aimed to determine the phytochemical content and antiradical activities of L. sarmentosa root fractions. Fractions were obtained using solvents with different polarities. The sample was extracted by maceration using ethanol, and the extract was fractionated by column chromatography using hexane, chloroform, ethyl acetate, and methanol. The chemical content of each fraction was identified using LCMS/MS. The antiradical activity was performed against DPPH using a UV-Visible spectrophotometer. The LCMS/MS analysis results indicated that each fraction contained different percentages of compounds, such as alkaloids, terpenoids, phenylpropanoids, stilbenes, flavonoids, tannins, fatty acids, and steroids. Ostruthin was a compound detected in all fractions with a retention time of 20,917 minutes and was considered a marker compound from the roots of L. sarmentosa. The antiradical activity assay showed that the methanol fraction had the best activity with an IC50 value of 83.42 ppm. The IC50 data shows that increasing the percentage of alkaloid compounds increased their antioxidant activity.